Effects of tamoxifen on normal breast tissue histological composition: Results from a randomised six‐arm placebo‐controlled trial in healthy women. Issue 11 (22nd January 2023) - Gabrielson, Marike; Hammarström, Mattias; Bäcklund, Magnus; Bergqvist, Jenny; Lång, Kristina; Rosendahl, Ann H; Borgquist, Signe; Hellgren, Roxanna; Czene, Kamila; Hall, Per
Abstract: Tamoxifen prevents recurrence of breast cancer and is suggested for preventive risk‐reducing therapy. Tamoxifen reduces mammographic density, a proxy for therapy response, but little is known about its effects in remodelling normal breast tissue. Our study, a substudy within the double‐blinded dose‐determination trial KARISMA, investigated tamoxifen‐specific changes in breast tissue composition and histological markers in healthy women. We included 83 healthy women randomised to 6 months daily intake of 20, 10, 5, 2.5, 1 mg of tamoxifen or placebo. The groups were combined to "no dose" (0‐1 mg), "low‐dose" (2.5‐5 mg) or "high‐dose" (10‐20 mg) of tamoxifen. Ultrasound‐guided biopsies were collected before and after tamoxifen exposure. In each biopsy, epithelial, stromal and adipose tissues was quantified, and expression of epithelial and stromal Ki67, oestrogen receptor (ER) and progesterone receptor (PR) analysed. Mammographic density using STRATUS was measured at baseline and end‐of‐tamoxifen‐exposure. We found that different doses of tamoxifen reduced mammographic density and glandular‐epithelial area in premenopausal women and associated with reduced epithelium and increased adipose tissue. High‐dose tamoxifen also decreased epithelial ER and PR expressions in premenopausal women. Premenopausal women with the greatest reduction in proliferation also had the greatest epithelial reduction. In postmenopausal women, high‐dose tamoxifen decreased the epithelial area with no measurable density decrease. Tamoxifen at both low and high doses influences breast tissue composition and expression of histological markers in the normal breast. Our findings connect epithelial proliferation with tissue remodelling in premenopausal women and provide novel insights to understanding biological mechanisms of primary prevention with tamoxifen. Abstract : What's new? Tamoxifen is used to prevent breast cancer recurrence or in some cases for primary prevention of breast cancer. Here, the authors tested the effect of different doses of tamoxifen on breast tissue in healthy women. They found that tamoxifen at both low and high doses changed the composition of breast tissue in premenopausal women, decreasing density by reducing epithelial tissue and increasing adipose tissue. It also altered hormone receptor expression in breast epithelial tissue. The results suggest that tamoxifen could be effective at lower doses to prevent breast cancer.